Scientific And Literary Progress During Medieval Period With Special Reference To Medicine (750-945) - Hussain, Ashaq (Ar Raniry : International Journal of Islamic Studies, 2015)
During the Abbasid period, Muslim culture and civilization was at its zenith. It was a period of economic prosperity and of great intellectual awakening. The Abbasid Caliphate provided the most congenial atmosphere for the advancement of learning and education. In fact, the reign of Mamun-ar-Rashid who has deservedly been called the 'Augustus of Arabs' formed the culmination of the intellectual achievements of the Muslims. He was followed by a brilliant succession of Caliphs who continued his work. Muslims gained access to the Greek medical knowledge of Hippocrates, Discords, and Galen through the translations of their works in the seventh and eighth centuries. These initiatives by Muslims could be seen in the different aspects of the healing arts that were developed. The translation movement of the twelfth century in Latin Europe affected every known field of science, none more so than medicine. The present paper is an attempt to give a detailed contribution of Muslims to science with special reference to medicine. It is in this context the present paper has been analyzed.